2023
DOI: 10.3390/bioengineering10030304
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated In Vivo/In Vitro Protein Production Platform for Site-Specific Antibody Drug Conjugates

Abstract: The XpressCF+® cell-free protein synthesis system is a robust platform for the production of non-natural amino acids containing antibodies, which enable the site-specific conjugation of homogeneous antibody drug conjugates (ADCs) via click chemistry. Here, we present a robust and scalable means of achieving a 50–100% increase in IgG titers by combining the high productivity of cell-based protein synthesis with the unique ability of XpressCF+® reactions to produce correctly folded and assembled IgGs containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Previously, we demonstrated that our E. coli strain SBDG419, which has been engineered to have an oxidizing cytoplasm, could express a variety of LCs that could be incorporated into antibodies produced in CFPS reactions. 26 The high titer and productivity observed in the SBDG419 strain suggested that it could be a promising platform for producing antibody fragments and full-length antibodies potentially containing nnAAs. Therefore, an expression screen of several therapeutically relevant proteins without nnAAs was performed in this strain to find potential scaffolds for nnAA incorporation, including a scFv, 29 an anti-CD3 antibody Fab, 30 and a full IgG complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we demonstrated that our E. coli strain SBDG419, which has been engineered to have an oxidizing cytoplasm, could express a variety of LCs that could be incorporated into antibodies produced in CFPS reactions. 26 The high titer and productivity observed in the SBDG419 strain suggested that it could be a promising platform for producing antibody fragments and full-length antibodies potentially containing nnAAs. Therefore, an expression screen of several therapeutically relevant proteins without nnAAs was performed in this strain to find potential scaffolds for nnAA incorporation, including a scFv, 29 an anti-CD3 antibody Fab, 30 and a full IgG complex.…”
Section: Resultsmentioning
confidence: 99%
“… 14 Due to these challenges with periplasmic expression, we focused on the synthesis of mAbs and mAb fragments in the oxidizing cytoplasm of an E. coli strain that was redox optimized for high-level expression of antibody light chain (LC) lacking nnAAs in the cytoplasm. 26 Production of this LC is relatively straightforward because it requires overexpression of only a single protein in the proper redox environment. Notably, it was also shown that the same LC will express poorly in a strain background exhibiting a wild type, reducing cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The XpressCF+ platform enables easier incorporation of non-natural amino acids and conjugates, as well as reduces protein heterogenicity and facilitates biosynthesis of structurally complex precisely assembled products. At present, Sutro has four conjugates and bsAbs in its portfolio that have been produced with the XpressCF+™ technology and continues to expand its inf luence by collaborating with other companies [98,99].…”
Section: Discussionmentioning
confidence: 99%